How much preoperative ROM and FC is a predictor for poor result after total knee arthroplasty in hemophilic arthropathy? - Jiang, Hongyu; Chang, Xueke; Yu, Fubin; Li, Wei; Fang, Naihan; Man, Jianzhi; Guo, Kangshu; Meng, Hongzheng; Zhang, Wenqiang (Frontiers in Surgery, 2025)
AimWe aimed to explore the threshold of preoperative range of motion (ROM) and flxion contacture (FC) as a predictor of Poor knee function after TKA.MethodA retrospective analysis was conducted on 84 Patients with haemophilia (PWH) (113 knees) who underwent knee arthroplasty in our hospital from January 2010 to December 2020 (mean follow-up 70.7 ± 22.4 months). General information, hemophilia information, surgical information, follow-up information were collected. Knees were divided into two groups: Group poor (41 knees) and Group excellent (72 knees). In the clinical evaluation, the FC, ROM and American Society Knee clinical Score (KSC), American Society Knee functional Score (KSF), Hospital for Special Surgery (HSS) scores were used preoperatively and at the final follow-up visit. Receiver operating characteristics (ROC) analysis was used to analyze the threshold of preoperative ROM and FC as a predictor of Poor knee function after TKA.ResultPostoperative knee joint KSC, KSF, and HSS scores, as well as ROM and reduction in FC deformities at the last follow-up, improved significantly compared to preoperative levels. A notable correlation was observed between ROM and FC and the outcome of knee arthroplasty. The cutoff value of preoperative fexion contracture and ROM for poor knee function at last-follow up was 16.5° and 61.5°.ConclusionThe study concludes that the efficacy of knee joint replacement surgery in hemophilia patients is influenced by the pre-ROM and Pre-FC. The better the pre- ROM, the better the knee efficacy. The greater the pre- flexion contracture degree, the worse the knee efficacy.